(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Many teaching techniques have been used to improve students’ reading comprehension level in advanced ESP courses. However, these techniques focus only on the product and process of reading comprehension. Therefore, these techniques are not adequate enough since they disregard certain teaching factors that stimulate students to become efficient readers of ESP texts. In addition, most Iraqi advanced ESP courses rely heavily on the conventional techniques of reading instruction, which simply involve reading the text, explaining its meaning, and answering its questions. As a result, students in ESP courses need novel techniques that enable them to have full comprehension of what they have already read. One of such techniques is believed to be the brainstorming adopted here as new orientation and most effective teaching technique which allows ESP students to freely express themselves and generate indefinite number of ideas on a topic relating to a given text prior to the reading activity in class.